- EFEKTIVITAS PRP TERHADAP PERUBAHAN PROFIL LIPID DARAH TIKUS PUTIH JANTAN (Rattus Norvegicus) DIABETES MELITUS YANG DI INDUKSI STREPTOZOTOCIN: EFEKTIVITAS PRP TERHADAP PERUBAHAN PROFIL LIPID DARAH TIKUS PUTIH JANTAN (Rattus Norvegicus) DIABETES MELITUS YANG DI INDUKSI STREPTOZOTOCIN - Simarmata, Hans Pangestu; Saragih, Reyini Namora L.; Pasaribu, Jelita Pebriani; Sitorus, Josua Panangian; Chiuman, Linda; Janice, Janice (Universitas Jambi, 2021)
Diabetes mellitus is a disease problem in Indonesia due to the inability of the pancreas to produce insulin so the body's metabolic processes are disrupted. Platelet Rich Plasma is widely known to be a treatment in various fields of medicine because it contains many growth factors (GFs) which are useful for triggering growth, tissue, and cell regeneration. This study was conducted to determine the effectiveness of PRP at doses of 0.5, 1.0, and 1.5 ml/kg BW for improving lipid profiles. This study used an experimental method where PRP was made twice centrifugation, then divided into each treatment, each group was given twice a week for three weeks. The Shapiro-Wilk test was used for normally distributed data followed by the Kruskal-Wallis test followed by the analysis Mann-Whitney with a significant value of P <0.05, that is, there was an effect of PRP administration on improving levels of lipid profiles. The PRP dose of 0.5 ml/kg BW gave the effect of increasing the lipid profile except for HDL levels and a higher PRP dose was required to significantly increase HDL levels compared to the control group.Â Â